The Importance and Necessity of Liberalization of The Uzbekistan Economy - Eshkobilova Nargiza Mengnorovna; Turabayeva Kimiyokhon Urazbekovna (Zien Journals, 2022)
This article describes the essence of economic liberalization, theoretical and practical measures to ensure economic freedom in a market economy, the strategy of developed countries in liberalization and the stages of introduction of economic liberalization in Uzbekistan today, the pros and cons.
Keywords: Economy; liberalism; liberalization; business